2021
DOI: 10.1609/aaai.v35i16.17665
|View full text |Cite
|
Sign up to set email alerts
|

Entity Structure Within and Throughout: Modeling Mention Dependencies for Document-Level Relation Extraction

Abstract: Entities, as the essential elements in relation extraction tasks, exhibit certain structure. In this work, we formulate such entity structure as distinctive dependencies between mention pairs. We then propose SSAN, which incorporates these structural dependencies within the standard self-attention mechanism and throughout the overall encoding stage. Specifically, we design two alternative transformation modules inside each self-attention building block to produce attentive biases so as to adaptively regularize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…BERT was built on the encoder of Transformer architecture [79] and trained with mask and next sentence prediction tasks, thus can "understand" text sentences and provide a strong base model for downstream tasks. In applications that need representation of input sequence such as sentiment analysis [80,81], intent prediction [82,83], POS Tagging [84], named entity recognition [85][86][87][88], event extraction [89][90][91], relation extraction [88,[92][93][94]. BERT encodes the input embedding sequence with selfattention mechanism in a bidirectional manner, which means a vector at any position can "see" all other vectors and represent its meaning based on the global context without step-by-step pro-jection.…”
Section: Applications Of DL Models In Nlpmentioning
confidence: 99%
“…BERT was built on the encoder of Transformer architecture [79] and trained with mask and next sentence prediction tasks, thus can "understand" text sentences and provide a strong base model for downstream tasks. In applications that need representation of input sequence such as sentiment analysis [80,81], intent prediction [82,83], POS Tagging [84], named entity recognition [85][86][87][88], event extraction [89][90][91], relation extraction [88,[92][93][94]. BERT encodes the input embedding sequence with selfattention mechanism in a bidirectional manner, which means a vector at any position can "see" all other vectors and represent its meaning based on the global context without step-by-step pro-jection.…”
Section: Applications Of DL Models In Nlpmentioning
confidence: 99%
“…Similar to our topic, many recent studies have focused on named entity recognition ( [7], [8], [9], [10]), relation extraction ( [11], [12], [13]), and the joint combination of both ( [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24]). Furthermore, [25] as well as [26] have shown that hierarchically using both tasks in a single pipeline can significantly improve the performance thus indicating that information from one task can be exploited by the other.…”
Section: Related Workmentioning
confidence: 99%
“…Previous generally effective methods for document-level RE are mainly graph-based models and transformerbased models. Graph-based models (Nan et al, 2020;Zeng et al, 2020Zeng et al, , 2021Xu et al, 2021b) gather entity information for relational inference with graph neural networks, and transformer-based methods (Zhou et al, 2021;Xu et al, 2021a;Zhang et al, 2021;Tan et al, 2022a) implicitly capture long-range dependencies. Recently, (Huang et al, 2022;Tan et al, 2022b) found that a large number of positive relations remain unlabeled in document-level RE datasets, especially unpopular relations.…”
Section: Related Workmentioning
confidence: 99%